Analisis faktor-faktor industri rumah tangga dan pengaruhnya terhadap peningkatan ekonomi keluarga (studi kasus: industri batik di Kecamatan Danau Teluk dan Pelayangan, Kota Jambi) - Sholatia Sholatia; Hardiani Hardiani; Etik Umiyati (Konsentrasi Ekonomi Sumberdaya Alam dan Manusia, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2021)
This study aims to: 1) To find out and analyze the development of per capita income, workers know the socioeconomic characteristics of the Batik Jambi home industry in DanauTeluk and Pelayangan districts. and 2) To determine the effect of capital, labor, age and length of business on the income of Batik Jambi home industry in Danau Teluk and Pelayangan districts. The data used in this study are primary data. The analytical method used is descriptive qualitative method, multiple regression analysis tool with the OLS method. Based on the results of the simultaneous test that only the variable capital and partial labor have a significant effect on the income of the head of the family, while the age and length of the business variable does not significantly influence the income of the owner of the owner of the batik industry in Danau Teluk and Pelayangan District.